Analisis Pengaruh Strategi Bisnis dan Ukuran Kinerja terhadap Kapabilitas Dinamis - Dyna Rachmawati (Jurnal Keuangan dan Perbankan, 2015)
Contingency studies have found that business strategies affect on performance indicators. Performance indicators mediate the effect of business strategies on business performance. This study use contingency theory and dynamic capability view to explain that business strategies promote dynamic capabilities indirectly through dynamic capabilities. Using 47 pharmaceutical strategic business units (SBUs), this study finds that business strategies have direct effect on dynamic capabilities. Business strategies increase dynamic capabilities indirectly through financial performance indicators. But, business strategies decrease dynamic capabilities indirectly through non-financial performance indicators